PENGARUH ETIKA KERJA ISLAM DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kab. Kutai Timur) - Heppy Harmoko; Hadi Sunaryo (UNIVERSITAS ISLAM MALANG, 2017)
AbstractThis study aims to determine the description of Islamic Work Ethics, JobSatidfaction and Employee Permformance, and to determine the Influence ofIslamic Work Ethics and Joba Satisfaction on Employee Performance. Thisresearch was conducted on empoyees at the Departemen of Women Empowermentand Child Protetion Kab. East Kutai. The number of respondents is 40 and is asensus study. The metod used in this study is qualitative data in tefor ofquestionnaires are quantized by means of interval scale in order to analyze itsinfluence through using multiple linear regression. The results showed that theaverage value of respondents' answers on Islamic Work Ethics is good enough,the average value of Job Satisfaction is still lacking, and the average value ofEmployee Performance is good enough. From this research is also known thatIslamic Work Ethics with indicators: Strong and reliable; Intention to work;Honest and fair; Work for yourself and others; Hard Work has a positive effect onEmployee Performance. Job Satisfaction with indicators: Salary; Facilities /equipment; The work itself; Recognition or praise has no effect on EmployeePerformance.Keyword : Islamic Work Ethics, Job Satisfaction, and Employee Performane.